The Potential of Leuweunggajah Village As A Tourist Village In The Ciledug District - Toni Ari Wibowo; Agung Setiawan; M Arief Haritsa (International Journal of Entrepreneurship and Tourism, 2023)
Leuweunggajah Village, Ciledug District, is one of the villages that have untapped potential for tourist objects and attractions, so an analysis of the potential and opportunities as a tourist village must be carried out. To obtain potential opportunities for potential tourist objects and attractions in Leuweunggajah village, it is necessary to data collection through observation, interviews, and documentation. The results of the data collection that has been carried out will be analyzed and described according to current conditions and circumstances. Leuwuenggajah Village has 9 (nine) potential tourist objects and attractions including the Old Sacred Well, the Baitussu'ada Jami Mosque, the Red Brick and Kentongan of the Baitussu'ada Jami Mosque, the Dome of the Baitussu'ada Jami' Mosque, the Habib Toha Grave, the Tradition of selling on Fridays. 'at Kliwon, Sugar Factory in Leuwunggajah village, Ciledug Station, Ciledug District, Cirebon Regency, MSME activity programs: Seed house, Geol Crackers, Peanuts, and Umpet so that Leuweunggajah village has the opportunity to become a tourist village in Ciledug district which of course must be supported by the village government, community leaders, the role of the Putri Wanaliman Farming Women's Group (KWT) and educational institutions.